Optimización del sistema de explotación para la extracción de materiales áridos y pétreos en el área minera “El Huato”, código 600155, ubicada en las parroquias malacatos y san pedro de vilcabamba, cantón y provincia de Loja. - Benavides Ochoa, Diego Xavier (2016)
The " EXPLOITATION SYSTEM OPTIMIZATION FOR REMOVAL OF MATERIALS AGGREGATES AND STONY Of THE MINING AREA “THE HUATO” CODE 600155, LOCATED IN THE MALACATOS PARISHES AND SAN PEDRO DE VILCABAMBA, CANTON AND PROVINCE OF LOJA", was developed by diagnosis Preview of the area involved, making the recognition of extractive activities currently carried out in the mining area "the Huato" was essential to know each of these processes as this allowed to determine what can be or not optimization. Aggregates and stone materials for a long time are the basic raw material in urban development and construction, with the supply and demand for this type of increasing resources. There are many deposits of these materials and are almost always conditioned by its topography and geology that are fundamental factors that were analyzed for the project. The current features of the operating system are not optimal, since mining operations are carried out under unfavorable conditions within the bed of the river and not the entire deposit of building materials is used; The object of this project was to develop an alternative economic technique that benefits the company by improving working conditions, increasing production and reducing operating costs using staff, machinery and equipment currently available. Presenting a different current alternative and has been evaluated technically and economically without underestimating the environmental aspect; not only benefits the company but will allow a balance between mining activity and the environment which leads to the conservation of the same, making this new operating system favorable for the development of mining activities proposed. Keywords: exploitation system, optimization, alluvium, performance, cycle, extraction, loading, hauling, accumulation, floodplain.